2019
DOI: 10.1111/apa.14888
|View full text |Cite
|
Sign up to set email alerts
|

Health Extension Workers’ diagnostic accuracy for common childhood illnesses in four regions of Ethiopia: a cross‐sectional study

Abstract: Aim: The Ethiopian primary care of sick children is provided within the integrated Community Case Management of childhood illnesses by Health Extension Workers (HEW). There is limited knowledge whether this cadre correctly assess and classify common diseases. The aim was to study their ability to correctly classify common childhood illnesses.Methods: A survey was conducted from December 2016 to February 2017 in four regions of Ethiopia. Observations of the HEWs' assessment and classification of sick children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 24 publications
(28 reference statements)
4
29
0
Order By: Relevance
“…Further, treatment with Ready-to-Use Therapeutic Food was not provided according to the measurements or classification. In the sub-study reporting disease classification also by re-examination of the same sick children as in this study, only 40% were correctly classified for malnutrition [17]. The physical danger signs, i.e., visible severe wasting and pitting edema, were also assessed in few children.…”
Section: Plos Onementioning
confidence: 73%
See 2 more Smart Citations
“…Further, treatment with Ready-to-Use Therapeutic Food was not provided according to the measurements or classification. In the sub-study reporting disease classification also by re-examination of the same sick children as in this study, only 40% were correctly classified for malnutrition [17]. The physical danger signs, i.e., visible severe wasting and pitting edema, were also assessed in few children.…”
Section: Plos Onementioning
confidence: 73%
“…Interventions have been implemented to improve the quality of community case management programs, showing that performance reviews and clinical mentoring were successful [13], while supportive supervision had less evident effect on quality of services [10,13]. A recent study, based on the same larger survey as this article, showed that the health extension workers' diagnostic accuracy was low [17]. The utilization of child curative services at the health post has also remained on a relatively low level [7].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…This evaluation is linked to an ongoing process evaluation as well as in-depth substudies that address the Women’s Development Army leaders’ promotion of maternal and child health, quality of care provided by HEWs, equity and geographic distribution of service utilisation that can also offer further explanations to the observed lack of effect. 18 40 42 43 Given the overall low care-seeking for childhood illnesses in this study continued efforts are needed to strengthen the primary care services for under-five children.…”
Section: Resultsmentioning
confidence: 96%
“…The quality of iCCM services measured at baseline was low, and it is unlikely to have been improved by the training, supervision and infrequent clinical mentoring supported by OHEP. 18 …”
Section: Discussionmentioning
confidence: 99%